Increasing Literacy and investment assistance in Sharia Financial institutions for Muslim Study Groups in the Suburbs of Palangka Raya City - Hidayati, Tri; Helim, Abdul; Fikriyyah, Ulya Nurul; Munawwarah, Siti; Khisan, Zariatul; Asfirah, Evi; Fadholina, Cania Ainusifa; Haikal, Fikri (PT FORMOSA CENDEKIA GLOBAL, 2024)
The aim of this activity is to increase understanding of sharia financial concepts, encourage responsible financial management, facilitate access to sharia financial products, increase awareness of sustainability and economic ethics, reduce financial risks and increase economic resilience, and empower the community through sharia financial literacy. The activity was carried out using the lecture and mentoring method in Petuk Ketimpun Village, the participants were the Muslim recitation group at the Nurul Iman Mosque. As a result, participants' sharia financial literacy increased.